Research influence of contact network voltage parameters on energy indicators for operation of auxiliary machines of vl-80k, t series (Transport systems and technologies, 2019)
The article proposes and implements a mathematical model of an induction motor in "brake coordinates". This will allow the application of this model in the study of the operation of the induction motor under conditions of asymmetry of the system of supply voltages and in the non-sinusoidal state of these voltages. In the power supply system of the induction motors of the auxiliary drive of electric locomotives of the VL-80T, K series, a phase splitter is used to convert a single-phase supply voltage into a three-phase voltage system. It is an induction motor with a short-circuited rotor, operating in the set mode as a generator. For the established mode, it is proposed to replace the phase splitter with a system of three-phase asymmetric EMF. For this purpose, vector diagrams of phase EMFs are calculated and constructed, from which the amplitudes and phases of each phase of EMF are determined. A model of an auxiliary electric locomotive drive system was proposed and implemented in the MATHCad software environment using the obtained model of induction motor in "braked coordinates" and the obtained phase EMF system. On the obtained model, the influence of the asymmetry of the system of supply voltages of the induction motor on the energy performance of the drive was initially investigated. Then, considering the parameters of the voltage of the contact network, the effect of the asymmetry and non-sinusoidal power supply system on the specified indicators of the drive of the auxiliary machines was investigated. It is proposed to replace the phase splitter with a static converter to improve these performance in the auxiliary drive system.
Keywords: locomotive power factor, non-sinusoidal and voltage asymmetry, auxiliary drive